Australian survey of current practice and guideline use in adult cancer pain assessment and management: The community nurse perspective. Issue 1 (March 2015) - Phillips, Jane L.; Lovell, Melanie; Luckett, Tim; Agar, Meera; Green, Anna; Davidson, Patricia
Summary Background Cancer pain remains a major public health concern. Despite effective treatments being available to manage the majority of cancer pain, this debilitating symptom is frequently under treated. As cancer has becomes a chronic disease a range of health professionals, including community nurses in Australia are increasingly caring for people living with cancer related pain. Yet, little is known about community nurses capacity to assess and manage cancer pain in accordance with best available evidence. Objectives This study aimed to: identify the barriers and facilitators to adult cancer pain assessment and management as perceived by Australian health professionals; identify if cancer pain guidelines are currently used; identify barriers and facilitators to guideline use; and establish the need for Australian cancer pain guidelines. This article reports on community nurses' perceptions of managing cancer pain in the community setting. Methods A cross-sectional survey was administered online. Invitations were circulated via peak bodies and clinical leaders seeking the views and experiences of health professionals involved in caring for people living with cancer pain. Descriptive statistics were used to summarise the quantitative data, and thematic content analysis were used to describe the qualitative data. Results Sixty-two community nurses responded to the survey, representing 29% of the total sample. These participants reported high levels of adherence to accepted cancer pain management practices in their workplace, with 71% nominating the Palliative Care Therapeutic Guideline V.3 as being most frequently used to manage community patients' cancer related pain. Key barriers to effective cancer pain management in the community were: difficulties accessing non-pharmacological interventions (89%), lack of coordination by multiple providers (89%), and impact of distance on ability to access pain-related services for patients (86%). Conclusion A range of system, health professional and consumer barriers limit access to best available treatment in the community setting for people with cancer pain. A clinical pathway that gives step-by-step guidance on evidence-based practice along with an evaluation framework may be the best way of enabling community nurses to ensure their patients with cancer related pain have access to best available care.